What Makes a Good Teacher? - David L. Going (Washington University Journal of Law & Policy, 2017)
This Article explores Judge Barry Schermer’s approach to teaching, both in the courtroom and in the classroom. Going recounts some of his interactions before Schermer during his practice as well as teaching alongside him at Washington University School of Law. The Author narrows on Schermer’s performance as an animated and committed teacher, as well as his kind and approachable demeanor, as ways of drawing both students and advocates into the intricacies of bankruptcy law.
Keywords: Washington University School of Law; Bankruptcy Code; Judge Schermer